Spindle pole body-anchored Kar3 drives the nucleus along microtubules from another nucleus in preparation for nuclear fusion during yeast karyogamy - Gibeaux, Romain; Knop, Michael (Genes & development, 2013)
Nuclear migration during yeast karyogamy, termed nuclear congression, is required to initiate nuclear fusion. Congression involves a specific regulation of the microtubule minus end-directed kinesin-14 motor Kar3 and a rearrangement of the cytoplasmic microtubule attachment sites at the spindle pole bodies (SPBs). However, how these elements interact to produce the forces necessary for nuclear migration is less clear. We used electron tomography, molecular genetics, quantitative imaging, and first principles modeling to investigate how cytoplasmic microtubules are organized during nuclear congression. We found that Kar3, with the help of its light chain, Cik1, is anchored during mating to the SPB component Spc72 that also serves as a nucleator and anchor for microtubules via their minus ends. Moreover, we show that no direct microtubule-microtubule interactions are required for nuclear migration. Instead, SPB-anchored Kar3 exerts the necessary pulling forces laterally on microtubules emanating from the SPB of the mating partner nucleus. Therefore, a twofold symmetrical application of the core principle that drives nuclear migration in higher cells is used in yeast to drive nuclei toward each other before nuclear fusion.